Approach to the Paediatric Patient With Suspected Pheochromocytoma or Paraganglioma Versus Neuroblastoma - Hendriks, A Emile J; Burns, Charlotte; Fleming, Ben; Harper, Ines; Hook, Elizabeth; Armstrong, Ruth; Pamporaki, Christina; Eisenhofer, Graeme; Murray, Matthew J; Casey, Ruth T (The journal of clinical endocrinology and metabolism, 2025)
Catecholamine-producing tumors of childhood include neuroblastic tumors, phaeochromocytoma, and paraganglioma (PPGL). PPGL and neuroblastic tumors can arise in similar anatomical locations and clinical presentations can overlap, resulting in diagnostic challenges. Distinguishing between these tumor types is critical as management and long-term surveillance strategies differ depending on the diagnosis. Herein we describe 2 clinical cases and illustrate key considerations in the diagnostic workup of a neuroblastoma vs PPGL for patients presenting with adrenal, pelvic, and retroperitoneal masses in childhood.